Kontribusi Agroforestri Terhadap Pendapatan Petani Di Desa Sukoharjo 1 Kecamatan Sukoharjo Kabupaten Pringsewu - Rafin Olivi; Rommy Qurniati; Firdasari Firdasari (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Agroforestry is one form of land use in multicrown consisting of a mixture of the trees, shrubs with an annual or plants often accompanied by cattle in one plots of land. System agroforestri of benefits economical and ecological that matter to farmers, one of which can provide income for farmers. Research is to calculate what large contribution agroforestri and to know faktor-faktor affecting farmers income. The study is done in the Village Sukoharjo 1 Sub-District Sukoharjo District Pringsewu. Contribution agroforestry expressed in the percentage revenue agroforestri with total revenue farmer. To analyze factors affecting farmers' income analyzed by linear regression of multiple.From the reckoning, contribution agroforestri against revenue is 88.31% or Rp 50,14,.696.00/kk/ha/year and results regression analysis variables influential real against earnings agroforestri is age, the area of field, the amount of labor, tribe, religion, landslope and credit assistance. Keywords: agroforestri, the contribution of income, income factors